MXenes: state-of-the-art synthesis, composites and bioapplications. Issue 23 (31st May 2022) - Fadahunsi, Adeola A.; Li, Chengpan; Khan, Muhammad Imran; Ding, Weiping
Abstract : MXenes have shown great potential in a variety of domains. This review elaborates the up-to-date synthesis methods, physicochemical properties and biological applications of MXene-based nanocomposites, as well as the practical hurdles and prospects. Abstract : MXenes have shown significant potential in a multitude of scientific domains as they provide substantial benefits over carbon graphene, such as ease of production and functionalization, large surface area, adjustable properties, biocompatibility and hydrophilicity. The morphologies and physicochemical properties of MXenes vary with the synthesis procedures and conditions. Very recently, unique hybrid MXene-based nanocomposites have been produced and applied in a variety of fields. Herein, we review the synthesis of MXenes from traditional chemical exfoliation methods to newly developing fluoride-independent hydrothermal methods, summarize the properties of the synthesized MXenes, including stability and oxidative sensitivity, and outline emerging approaches for MXene-based nanocomposites. We also elaborate the up-to-date bio-applications of MXenes in photothermal therapy, bio-imaging, sensing, and drug delivery, as well as the practical hurdles that must be addressed.